Reliable Post Disaster Services over Smartphone Based DTN An End-to-End Framework - Basu, Souvik; Roy, Siuli; Das Bit, Sipra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book proposes a framework and strategies for reliable end-to-end post-disaster services using smartphone-based delay-tolerant networks, which can operate even in the absence of conventional network connectivity. It explores various aspects of this challenge, ranging from accurate need assessment, to timely need accumulation, efficient resource allocation, and reliable data dissemination. The book offers insightful reading for all technologists and researchers working in the domain of ICT-based disaster management in developing countries, and will help them grasp the challenges involved in providing post-disaster services in an extremely difficult network scenario, while also offering possible solutions. The book will also benefit disaster management authorities, government agencies, NGOs and other stakeholders, helping them enhance their preparedness through the intelligent use of wireless technologies coupled with smart devices.
Preface -- Acknowledgements -- Introduction -- Post Disaster Need Assessment -- Need Accumulation over DTN -- Resource Planning -- Reliable Data Dissemination over DTN -- Conclusion.
Keywords: Computational intelligence; Wireless communication systems; Mobile communication systems; Telecommunication; Computer networks .; Security systems; Computational Intelligence; Wireless and Mobile Communication; Communications Engineering, Networks; Computer Communication Networks; Security Science and Technology